First passage statistics for diffusing diffusivity. (28th December 2018) - Sposini, Vittoria; Chechkin, Aleksei; Metzler, Ralf
Abstract: A rapidly increasing number of systems is identified in which the stochastic motion of tracer particles follows the Brownian law yet the distribution of particle displacements is strongly non-Gaussian. A central approach to describe this effect is the diffusing diffusivity (DD) model in which the diffusion coefficient itself is a stochastic quantity, mimicking heterogeneities of the environment encountered by the tracer particle on its path. We here quantify in terms of analytical and numerical approaches the first passage behaviour of the DD model. We observe significant modifications compared to Brownian–Gaussian diffusion, in particular that the DD model may have a faster first passage dynamics. Moreover we find a universal crossover point of the survival probability independent of the initial condition.